Efficacy of Oil Pulling in the Management of Oral Submucous Fibrosis: A Preliminary Study - Swatantra Shrivastava; Shushma Gurumurthy; Bharati Doni; Ruchi Agrawal; Santosh Rayagouda Patil; Hesham Shokry Ismail; Mohammad Khursheed Alam (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the effectiveness of oil pulling in the management of oral submucous fibrosis (OSMF). Material and Methods: A total of 62 patients clinically and histopathologically diagnosed as OSMF were incorporated in the present study. The subjects are randomly divided equally into two groups, Group A (oil pulling group) and Group B (placebo group). Subjects in Group A were asked to perform OP with sesame oil on an empty stomach in the morning for 3 months and Group B was given placebo capsules for 3 months. Assessment of various clinical parameters was done regularly, and data were analyzed using the Chi-square test. Results: Eighty-two percent had a habit of betel nut chewing, while 18% of the patients had tobacco chewing habits, which were among the main causative factors for OSMF. Clinical improvements in mouth opening, tongue protrusion, difficulty in speech and deglutition, and burning sensation were significant in the Group A. None of the patients reported any discomfort or side effects. The symptoms were not severe in nature and resolved in few days without stopping the therapy. Conclusion: Oil pulling can bring about significant clinical improvements in the symptoms like a mouth opening and tongue protrusion.